How Service Strategy and Quality Affect Customer Satisfaction at PT PELNI Sorong - Rizka Cintya Edwar (PT Agung Media Publisher, 2025)
This study investigates the influence of service marketing strategy and service quality on customer satisfaction at PT PELNI in Sorong City, Indonesia. As a state-owned enterprise in maritime transportation, PT PELNI faces growing customer expectations that demand continuous improvements in service delivery and marketing approaches. Understanding the factors that shape customer satisfaction is essential for enhancing competitiveness and loyalty in this industry. A quantitative research method with a descriptive-causative design was employed. The study involved 141 customers of PT PELNI Sorong, selected through a purposive sampling technique. Data were collected using a structured questionnaire, and analyzed using multiple linear regression with the assistance of SPSS version 20. The independent variables in this study were service marketing strategy and service quality, while the dependent variable was customer satisfaction. The results revealed that both service marketing strategy and service quality have a positive and statistically significant effect on customer satisfaction. Specifically, service marketing strategy contributed to strengthening customer engagement and perceived value, while service quality such as timeliness, reliability, and responsiveness directly influenced customer trust and overall satisfaction levels. The findings suggest that improving both the strategic and operational aspects of service delivery is critical to achieving customer satisfaction in maritime transportation. Future research may consider adding mediating variables such as brand image or customer loyalty, as well as exploring comparative studies across different regions or transportation providers.